Predicting Depression Based on Ego Weakness and Integrative Self-Knowledge with the Mediating Role of Defense Mechanisms and Psychological Pain - Karimi, Zahra; Karbalaee Mohammad Meygoni, Ahmad; Rezabakhsh, Hossein; Ataeifar, Robabeh (KMAN Counseling & Psychology Nexus, 2026)
The aim of the present study was to predict depression based on ego weakness and integrative self-knowledge with the mediating role of defense mechanisms and psychological pain. The research method was descriptive-correlational, and the aim was applied. The statistical population of this study included all men employed in a marine transportation company in the years 2020-2021, from which 378 participants were selected through convenience sampling. The research instruments included the Tangney et al. Self-Control Scale (2004), the Ghorbani et al. Integrative Self-Knowledge Scale (2008), the Andrews et al. Defense Style Questionnaire-40 (1993), the Orbach et al. Psychological Pain Scale (2003), and the Beck Depression Inventory (1961). The data of the present study were analyzed using structural equation modeling. By creating covariance between errors, the goodness-of-fit indices improved, and the resulting structural model fitted the collected data. There was a significant positive direct relationship between integrative self-knowledge and depression at the 0.01 level (P=0.010, β=0.453). There was a significant positive direct relationship between neurotic defense mechanisms and depression at the 0.05 level (P=0.014, β=0.174). There was a significant positive direct relationship between psychological pain and depression at the 0.01 level (P=0.010, β=0.622). Neurotic defense mechanisms mediated the relationship between integrative self-knowledge and depression (P=0.029, Z=2.17). The results of the present study showed that there was a significant direct relationship between integrative self-knowledge, neurotic defense mechanisms, and psychological pain with depression.